INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SELF-CONTROL SISWA TERHADAP DAMPAK NEGATIF MEDIA SOSIAL: Studi Fenomenologi di SMP Negeri 3 Rancaekek - Cindri Candrika; Muhammad Saepul Ulum; Delis Sri Maryati (Tarbiya Islamica, 2026)
The expansion of social media among adolescents has introduced complex challenges to the stability of self-control. This study aims to analyze the process of internalizing Islamic Education (PAI) values as an instrument for strengthening students’ self-control at SMP Negeri 3 Rancaekek in navigating the negative impacts of social media. A qualitative approach with a phenomenological method was employed. Primary data were gathered through in-depth interviews with students, complemented by participant observation and documentation studies to capture a comprehensive portrait of the subjects’ lived experiences. The findings indicate that the internalization of Islamic values within the school transcends mere cognitive understanding, transforming into a spiritual consciousness that functions as a digital ethical filter. Students conceptualize Islamic teachings as a foundational framework for self-regulation in managing social media usage duration and maintaining communication etiquette in cyberspace. The efficacy of this process is significantly bolstered by the role of PAI teachers as exemplary figures (uswah hasanah) and the support of the school ecosystem through religious extracurricular activities that foster a culture of mutual moral guardianship (tashiyah). This research underscores that reinforcing religiosity through Islamic Education contributes substantially to the formation of mental resilience and digital ethics among students amidst the dynamic flow of social media information.